Does early phase of business cycle moderate small business success? Empirical evidence from Malaysia - Abdullah, Moha Asri; Azam, S. M. Ferdous (Institute of Research and Journal, 2016)
The purpose of this research is to assess the moderating effect of enterprise early phase in financial practice towards business success in Malaysian small business. The early phase is defined via a length of operation of an enterprise. To achieve the research objectives, this study employed survey method where the enterprises with a different length of operation were considered for the analysis. In fact, a sample of 302 data was evaluated as the final sample size for the current research. Using Structural Equation Modelling (SEM), moderating effects were observed to test the hypotheses. The results indicate that the enterprise early phase does have different moderating roles in financial practice to guide the business success in Malaysian small business. Thus, this research conveys an understanding to the entrepreneurs regarding the differences of enterprise early phase to achieve the business success swiftly. Finally, this research brings some implications to the policymakers and regulators as well.